2006
DOI: 10.1021/jp0571473
|View full text |Cite
|
Sign up to set email alerts
|

Novel Core−Shell-Structured Li[(Ni0.8Co0.2)0.8(Ni0.5Mn0.5)0.2]O2 via Coprecipitation as Positive Electrode Material for Lithium Secondary Batteries

Abstract: We have successfully synthesized a spherical core-shell structure based on Li[(Ni0.8Co0.2)0.8(Ni0.5Mn0.5)0.2]O2 via a coprecipitation route. According to the careful examination by scanning electron microscopy (SEM), transmission electron microscopy energy-dispersive spectroscopy (TEM-EDS), and X-ray diffraction (XRD), it was found that the core-shell particle consisted of Li[Ni0.8Co0.2]O2 as the core and Li[Ni0.5Mn0.5]O2 as the shell, of which the thickness was estimated to be 1 to approximately 1.5 microm. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
51
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 99 publications
(54 citation statements)
references
References 19 publications
(41 reference statements)
2
51
0
1
Order By: Relevance
“…In addition, these nickel-rich cathodes suffer from gradual capacity fading with cycling due to their structural instability, which is ascribed to the successive phase transitions from hexagonal 2 (H2) to hexagonal 3 (H3) phases when large amounts of Li + are extracted from the host structure [28][29][30][31][32][33]. To solve these problems, various approaches including structure tuning [34][35][36], substitution [37][38][39], and surface coating [40][41][42][43][44][45] have been proposed. Metal oxides such as Al 2 O 3 [46,47], ZrO 2 [48], MgO [49], have been studied as coating materials.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, these nickel-rich cathodes suffer from gradual capacity fading with cycling due to their structural instability, which is ascribed to the successive phase transitions from hexagonal 2 (H2) to hexagonal 3 (H3) phases when large amounts of Li + are extracted from the host structure [28][29][30][31][32][33]. To solve these problems, various approaches including structure tuning [34][35][36], substitution [37][38][39], and surface coating [40][41][42][43][44][45] have been proposed. Metal oxides such as Al 2 O 3 [46,47], ZrO 2 [48], MgO [49], have been studied as coating materials.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, a core-shell approach 11 resulted in a nickel-rich LiNi 0.8 Co 0.1 Mn 0.1 O 2 core that delivered high capacity at high voltage, and a manganese-rich LiNi 0.5 Mn 0.5 O 2 shell that stabilized the surface of the material. However, owing to the structural mismatch and the difference in volume change between the core and the shell, a large void forms at the core/shell interface after long-term cycling, leading to a sudden drop in capacity 12,13 . We also demonstrated that this structural mismatch could be mitigated by nano-engineering of the core-shell material, where the shell exhibits a concentration gradient 14-16 .…”
mentioning
confidence: 99%
“…leading to a sudden drop in capacity 12,13 . We also demonstrated that this structural mismatch could be mitigated by nano-engineering of the core-shell material, where the shell exhibits a concentration gradient [14][15][16] .…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Temperature increase has been reported to influence the structure stability, 2,3,6 the working quality of the core/shell bionanoactuators, 7 and light emission of CdSe/ CdS nanocrystals. 1 The melting point of the coated nanocores can be modified by the technique of surface coating, in which lower melting point [6][7][8] and superheating and supercooling 5 have been achieved.…”
mentioning
confidence: 99%